Constant temperature and humidity accelerated test method for thermal discoloration performance of lithium copper foil
Patent Information
- Application Number
- CN202610671102.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-15
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2046-05-15
AI Technical Summary
[0005]本发明提供了锂电铜箔热变色性能的恒温恒湿加速测试方法,旨在解决现有技术中宏观变色现象与微观结构演变之间关系不明确、缺乏连续且原位观测数据链的技术问题
1、通过构建多模态同步原位观测体系,首次实现了锂电铜箔在恒温恒湿加速老化过程中宏观颜色变化与微观结构演变的高精度、连续、同区域、同时间基准的关联记录;
Smart Images

Figure CN122193119B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of materials testing and analysis technology, specifically relating to a constant temperature and humidity accelerated testing method for the thermochromic properties of lithium battery copper foil. Background Technology
[0002] As a key material for the negative electrode current collector in lithium-ion batteries, the thermal discoloration performance of copper foil directly affects the interfacial stability and long-term cycle reliability of the battery. Under high temperature and humidity conditions, the copper foil surface is prone to physicochemical changes such as oxidation, corrosion, or decomposition of organic residues, leading to abnormal macroscopic color and potentially inducing problems such as increased interfacial impedance and increased risk of lithium plating. Therefore, accurate assessment of the thermal discoloration behavior of copper foil has become an important basis for material screening and process optimization. However, traditional testing methods typically rely on manual visual colorimetry or offline colorimeter measurements, which can only obtain discrete snapshots of macroscopic color change results, making it difficult to establish a dynamic correlation between the color change phenomenon and the evolution of the microstructure.
[0003] Isothermal and humidity accelerated aging tests are widely used to simulate the long-term service behavior of copper foil under harsh environments. This method induces surface reactions in a short period of time by controlling temperature and humidity parameters to predict material stability. Although such tests can reproduce macroscopic discoloration phenomena, they lack the ability to continuously track the same observation area and cannot simultaneously record the evolution trajectory of key features such as microstructure, grain boundary changes, or oxide layer growth. This makes it difficult for researchers to determine whether the color change is due to an accelerated surface oxidation rate, contaminant accumulation, or the expansion of microscopic defects.
[0004] In existing technologies, microscopic observation often employs offline sampling methods, where samples are retrieved at different time points and placed under independent microscopes for imaging. This not only disrupts the continuity of the testing environment but also prevents temporal comparisons of the same micro-region due to positioning errors. Furthermore, the lack of an automated correlation analysis mechanism between macroscopic colorimetric data and microscopic images necessitates subjective inference based on human experience, resulting in low efficiency and susceptibility to bias. Especially in high-throughput materials research and development scenarios, this fragmented characterization approach severely restricts the rapid analysis of thermochromic mechanisms and the accurate identification of failure initiation points. There is an urgent need for a testing method that can achieve in-situ, continuous, multi-scale observation of the same region under constant temperature and humidity conditions and automatically uncover macroscopic-microscopic correlation patterns. Summary of the Invention
[0005] This invention provides an accelerated isothermal and humidity-controlled testing method for the thermochromic properties of lithium-ion battery copper foil, aiming to solve the technical problems in existing technologies where the relationship between macroscopic color change phenomena and microstructural evolution is unclear, and there is a lack of continuous and in-situ observation data chains. The method constructs a closed-loop testing system integrating environmental control, multimodal synchronous acquisition, and dynamic correlation analysis. This enables high temporal resolution and high spatial consistency in the synchronous recording and quantitative correlation between the surface color change process of lithium-ion battery copper foil under controlled temperature and humidity conditions and its internal microstructural parameters such as grain orientation, grain boundary migration, oxide layer growth, and surface roughness evolution.
[0006] This invention provides a constant temperature and humidity accelerated testing method for the thermochromic properties of lithium battery copper foil, comprising: The lithium battery copper foil sample to be tested is fixed on a dedicated sample stage with a built-in temperature feedback sensor; The sample stage is placed inside a constant temperature and humidity test chamber; A multispectral imaging unit, a confocal microscopy unit, and a four-probe resistance measurement unit are set in the constant temperature and humidity test chamber, and all three are aligned with the same observation area of the lithium battery copper foil sample. Start the constant temperature and humidity test program, set the target temperature and target humidity, and maintain the environmental conditions continuously acting on the lithium battery copper foil sample; After the environmental conditions stabilize, the multispectral imaging unit, confocal microscopy unit, and four-probe resistance measurement unit are activated simultaneously to continuously sample the observation area at preset time intervals. The confocal microscopy unit acquires three-dimensional surface morphology data to calculate surface roughness parameters: arithmetic mean deviation, root mean square roughness, and maximum height, and combines image processing algorithms to identify grain boundary contours and grain size distribution. The four-probe resistance measurement unit records the curve of surface resistance changing over time. The CIELab chromaticity coordinates, surface roughness parameters, grain size distribution data, and surface resistivity data are strictly aligned according to timestamps to form a unified time-series multidimensional dataset. Based on the aforementioned time-series multidimensional dataset, a dynamic mapping function is established between the color change and the surface roughness increment, the average grain size growth rate, and the surface resistivity change rate.
[0007] Preferably, the multispectral imaging unit uses a 16-channel filter wheel spectral camera and the light source is a standard D65 daylight simulator.
[0008] Preferably, the confocal microscopy unit is a laser scanning confocal microscope, which is expanded through a stitching algorithm.
[0009] Preferably, the four-probe resistance measurement unit adopts a linear four-probe configuration.
[0010] Preferably, the dedicated sample stage is made of oxygen-free copper, with its surface treated by ultra-precision polishing, and a circular through hole is opened in the sample fixing area. The lithium battery copper foil sample is attached to the through hole by vacuum adsorption. The back of the sample is completely isolated from the internal environment of the cavity, and only the front is exposed to the test environment.
[0011] Preferably, the timestamp alignment is achieved through a hardware trigger signal. The main controller of the constant temperature and humidity test chamber sends a synchronous trigger pulse to the multispectral imaging unit, the confocal microscopy unit, and the four-probe resistance measurement unit at the beginning of each sampling cycle. Each unit completes a single data acquisition within a delay of less than 1 millisecond after receiving the pulse.
[0012] Preferably, the dynamic mapping function is constructed using a multivariate nonlinear regression model, whose input variables include surface roughness. and average grain size The output variable is the amount of color change. ; The model obtains regression coefficients by fitting historical test data using the least squares method, and evaluates the model's prediction accuracy using cross-validation. The model is considered effective when the root mean square of the prediction error is less than 0.5.
[0013] Preferably, during the constant temperature and humidity test, the oxygen concentration in the chamber is monitored in real time, and the oxygen concentration is determined by an electrochemical oxygen sensor; if the oxygen concentration is greater than the threshold, the nitrogen purging program is automatically started until the concentration returns to the set range.
[0014] Preferably, the thickness of the lithium-ion battery copper foil sample ranges from 4 micrometers to 8 micrometers, the initial surface roughness is controlled between 0.2 micrometers and 0.4 micrometers, and the standard deviation of the grain size distribution is less than 15% of the average value.
[0015] Preferably, the method further includes the steps of preparing a cross-section of the sample and performing transmission electron microscopy observation after the test: A thin slice with a thickness of less than 100 nanometers was cut from the center of the observation area using focused ion beam technology. The lattice distortion, dislocation density and oxide layer thickness in the near-surface region were observed using a high-resolution transmission electron microscope. The obtained microstructure information was then retrospectively correlated with the time-series data during the testing process.
[0016] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. By constructing a multimodal synchronous in-situ observation system, we have for the first time achieved a high-precision, continuous, regional, and time-based correlation record of macroscopic color changes and microstructural evolution of lithium battery copper foil during the accelerated aging process under constant temperature and humidity. 2. The dedicated sample stage design effectively eliminates sample deformation caused by thermal stress, ensuring spatial consistency of the observation area; the hardware-level time synchronization mechanism ensures the time alignment accuracy of multi-source data, avoiding misjudgment of causal relationships due to asynchronous sampling. 3. The established dynamic mapping function can quantitatively reveal the intrinsic relationship between color change and surface morphology, grain evolution and electrical performance degradation, providing a reliable data basis and theoretical support for the evaluation of thermal stability, optimization of production process and research on failure mechanism of lithium battery copper foil; 4. The entire testing process is conducted in a strictly controlled hypoxic environment, eliminating interference from non-target factors and improving the accuracy and repeatability of the test results. Attached Figure Description
[0017] Figure 1 This is a schematic diagram of the overall technical solution architecture of the present invention; Figure 2 This is a schematic diagram of the core principle framework of multimodal synchronous in-situ observation and dynamic correlation analysis in this invention; Figure 3 This is a flowchart illustrating the logical flow of the collaborative operation of the sample stage and multiple sensors under constant temperature and humidity accelerated testing environment in this invention. Figure 4 This is a flowchart illustrating the logical flow of the simultaneous acquisition of three modal data—multispectral imaging, confocal microscopy, and four-probe resistance measurement—in this invention. Figure 5 This is a logical flowchart of the construction of the temporal multidimensional data alignment and dynamic mapping function in this invention; Figure 6 This is a schematic diagram of the multi-level interaction relationships and data flow between key entities in the testing system of this invention. Detailed Implementation
[0018] refer to Figures 1 to 6 This invention provides an accelerated isothermal and humidity-controlled testing method for the thermochromic properties of lithium-ion battery copper foil. Its core lies in constructing a closed-loop testing system integrating environmental control, multi-modal synchronous acquisition, and dynamic correlation analysis. This system enables high temporal resolution and high spatial consistency in synchronous recording and quantitative correlation between the surface color change process of lithium-ion battery copper foil under controlled temperature and humidity conditions and its internal microstructural parameters such as grain orientation, grain boundary migration, oxide layer growth, and surface roughness evolution. The method strictly follows a pre-defined S-step sequence to ensure the logical rigor and repeatability of the technical process.
[0019] The method includes the following steps: S1, Fix the lithium battery copper foil sample to be tested onto the dedicated sample stage; S2, the sample stage is placed in the constant temperature and humidity test chamber; S3. A multispectral imaging unit, a confocal microscopy unit, and a four-probe resistance measurement unit are set in the constant temperature and humidity test chamber, and all three are aligned with the same observation area of the lithium battery copper foil sample. S4, start the constant temperature and humidity test program, set the target temperature and target humidity, and maintain the environmental conditions continuously acting on the lithium battery copper foil sample; S5. After the environmental conditions stabilize, the multispectral imaging unit, confocal microscopy unit, and four-probe resistance measurement unit are started simultaneously to continuously sample the observation area at preset time intervals. S6. The collected multimodal data is strictly aligned according to the timestamp to form a unified time-series multidimensional dataset; S7. Based on the time-series multidimensional dataset, establish a dynamic mapping function between the color change and the surface roughness increment, the average grain size growth rate, and the surface resistivity change rate.
[0020] In step S1, the lithium-ion battery copper foil sample to be tested is fixed on a dedicated sample stage. This dedicated sample stage is integrally machined from oxygen-free copper material, with a thermal conductivity uniformity greater than 0.5 degrees Celsius per square centimeter and a flatness error of less than 5 micrometers. This ensures highly uniform heat distribution throughout the testing process, avoiding non-target thermal stress deformation caused by localized temperature differences. A high-precision platinum resistance temperature sensor is embedded inside the sample stage, with a temperature measurement range covering 40 degrees Celsius to 120 degrees Celsius and a resolution of 0.01 degrees Celsius, used for real-time feedback of the sample stage surface temperature.
[0021] The sample stage surface undergoes ultra-precision polishing, with a surface roughness of less than 0.05 micrometers, to minimize the interference of background reflection on optical measurements. A circular through-hole with a diameter of 8 mm is made in the sample fixing area, extending through the thickness direction of the sample stage.
[0022] The lithium-ion battery copper foil sample to be tested is attached to the through-hole via vacuum adsorption. The vacuum adsorption system consists of a miniature diaphragm pump and a pressure regulating valve, and the adsorption pressure is precisely maintained at 80 kPa. This design ensures that the back side of the lithium-ion battery copper foil sample is completely isolated from the internal environment of the test chamber, while only the front side is exposed to the set temperature and humidity atmosphere, thereby eliminating the interference of back-side gas diffusion or condensation on the test results.
[0023] Meanwhile, the vacuum adsorption force is sufficient to resist the warping tendency of the sample during thermal expansion, ensuring that it remains flat and fixed in position throughout the entire testing cycle. The thickness of the lithium battery copper foil sample ranges from 4 micrometers to 8 micrometers, the initial surface roughness is controlled between 0.2 micrometers and 0.4 micrometers, and the standard deviation of the grain size distribution is less than 15% of the average value, so as to ensure the representativeness of the test sample in terms of microstructure and the consistency between batches.
[0024] In step S2, a dedicated sample stage containing the sample is placed into a constant temperature and humidity testing chamber. This chamber is a sealed stainless steel chamber with an electrolytically polished inner wall to reduce the risk of contaminant adhesion. The chamber is equipped with independent temperature and humidity control systems.
[0025] The temperature control system combines a semiconductor thermoelectric module with a liquid cooling cycle, achieving a temperature control range of 40°C to 120°C with a control accuracy of ±0.2°C. The humidity control system uses a high-precision mass flow controller to adjust the mixing ratio of dry nitrogen and saturated water vapor, achieving a relative humidity control range of 30% to 90% with a control accuracy of ±1.5%.
[0026] The cavity is equipped with multiple temperature and humidity sensors distributed at different heights and orientations around the sample stage to monitor the uniformity of the environmental field in real time. When the temperature difference between any two points exceeds 0.5 degrees Celsius or the humidity difference exceeds 3%, the control system automatically adjusts the angle of the airflow guide plate and the fan speed to enhance air circulation within the cavity and restore the uniformity of the environmental field.
[0027] In step S3, the multispectral imaging unit, confocal microscopy unit, and four-probe resistance measurement unit are precisely mounted within the temperature and humidity-controlled testing chamber and aligned together with the same observation area of the lithium-ion battery copper foil sample. This same observation area is located at the center of the sample and has an area of no less than 1 square millimeter to ensure that the acquired data is statistically representative and avoids edge effect regions. The multispectral imaging unit employs a 16-channel filter wheel-type spectrometer with a spectral response range covering 400 nanometers to 1000 nanometers, a spectral resolution of 20 nanometers, and a spatial resolution of 5 micrometers per pixel.
[0028] The light source was a standard D65 daylight simulator with a color temperature of 6500 Kelvin. Illuminance was maintained at 1000 lux via a closed-loop feedback system, with a fluctuation range of less than ±2%. The exposure time was fixed at 10 milliseconds to avoid brightness deviations caused by exposure time variations. The confocal microscopy unit employed a laser scanning confocal microscope with an excitation laser wavelength of 405 nm, an objective lens numerical aperture of 0.95, and a Z-axis piezoelectric actuator stepping accuracy of 10 nm. A single scan covered an area of 250 μm × 250 μm. Through a high-precision XY displacement platform and image stitching algorithm, nine adjacent sub-regions were seamlessly stitched together to ultimately form a complete 3D topographic image of 1 square millimeter.
[0029] The four-probe resistance measurement unit employs a linear four-probe configuration. The four probes are made of tungsten-rhenium alloy with a tip curvature radius of less than 5 micrometers, and the probe spacing is strictly controlled to 1 millimeter. During measurement, a constant DC current of 1 mA is applied to the two outer probes, while the two inner probes measure the voltage drop. The voltage sampling frequency is once per second. The sampling circuit features high input impedance and low-noise amplification characteristics to ensure accurate capture of microvolt-level signals.
[0030] In step S4, the constant temperature and humidity test program is initiated. The operator sets the target temperature and humidity via the human-machine interface, for example, 80 degrees Celsius and 60% relative humidity. Upon receiving the command, the control system sequentially activates the heating, cooling, humidifying, and dehumidifying modules, gradually bringing the environmental parameters within the chamber closer to the target values. When the fluctuation range of all temperature and humidity sensor readings within the chamber is less than the control accuracy limit for 5 consecutive minutes, the environmental conditions are considered stable, and the test enters the constant temperature and humidity testing phase. This phase continues to act on the lithium-ion battery copper foil sample until the preset test duration is completed, typically 24 to 120 hours.
[0031] In step S5, after the environmental conditions stabilize, the multimodal data acquisition system is synchronously started. The synchronization mechanism is achieved through a hardware trigger signal: the main controller of the constant temperature and humidity test chamber has a built-in high-stability clock source that generates a TTL-level synchronization trigger pulse at the beginning of each sampling cycle. This synchronization trigger pulse is simultaneously transmitted through shielded cables to the external trigger interfaces of the multispectral imaging unit, the confocal microscopy unit, and the four-probe resistance measurement unit.
[0032] Upon receiving a trigger pulse, each unit's internal acquisition circuit initiates a single data acquisition operation within a time window with a delay of less than 1 millisecond. The multispectral imaging unit acquires image sequences across 16 bands, the confocal microscopy unit completes a full Z-axis scan and XY-plane stitching, and the four-probe resistance measurement unit performs a voltage readout and resistance calculation. The preset time interval is no more than 30 seconds, with a typical value of 10 seconds, to ensure the capture of rapid dynamic processes in color and microstructure evolution. Each acquired data entry is accompanied by a unique timestamp assigned by the main controller, based on Coordinated Universal Time (UTC) with microsecond-level accuracy.
[0033] In step S6, all modal data streams are transmitted to the central data processing server. The server first verifies the consistency of the timestamps of each data packet, removing abnormal data frames with time offsets greater than 5 milliseconds due to communication delays. Subsequently, radiometric calibration and dark current correction are performed on the multispectral imaging data, converting it into an absolute reflectance spectrum. Based on the CIE 1931 standard observer function and the spectral power distribution of the D65 light source, the reflectance spectrum at each time point is integrated to calculate the corresponding CIELab chromaticity coordinates.
[0034] After denoising, plane fitting, and high normalization, the surface roughness parameters of the confocal microscopy data were calculated using the ISO4287 standard algorithm. (arithmetic mean deviation) (Root mean square roughness) and (Maximum height). Simultaneously, an image segmentation algorithm based on gradient magnitude and morphological operations is used to identify grain boundary contours, then statistically analyze grain areas and convert them into equivalent circle diameters to obtain the average grain size and its distribution histogram. Four-probe resistance measurement data, after temperature compensation, are converted into standardized surface resistivity values.
[0035] Finally, the CIELab chromaticity coordinates, surface roughness parameters, average grain size, and surface resistivity were strictly aligned according to timestamps to construct a time-inclusive database. ,temperature relative humidity The time-series cube with fields such as [field name] is stored in a structured database.
[0036] In step S7, a dynamic mapping function between color change and microstructure parameters is constructed based on the time-series multidimensional dataset.
[0037] Color change Defined as the Euclidean distance between the current chromaticity coordinates and the initial chromaticity coordinates, i.e. . , , for CIELAB color space coordinates at any moment , , For the initial CIELAB color space coordinates, the dynamic mapping function uses a multivariate nonlinear regression model, and its mathematical expression is: ; , , , , , , The regression coefficients to be fitted are . For the residual term, For surface roughness, This represents the average grain size. For thin-layer roughness, the model is fitted to historical test data using the least squares method to solve for the regression coefficients. To prevent overfitting, a 10-fold cross-validation method is used to evaluate the model's generalization ability: the dataset is randomly divided into 10 subsets, and the model is trained using 9 subsets in turn, with the remaining subset used for testing. This process is repeated 10 times, and the root mean square error of the prediction error is calculated. When the root mean square error is less than 0.5, the model is considered effective and can be used to predict the color evolution trend of new samples under similar test conditions.
[0038] Furthermore, the method also includes a microstructure retrospective verification step after the test. After the isothermal and humidity test, the sample is removed from the chamber and transferred to a focused ion beam device under an inert gas protective environment. At the center of the original observation area, a gallium ion beam is used with an accelerating voltage of 30 kV and a beam current of several hundred picoamperes to cut a thin sheet with a size of approximately 10 μm × 10 μm and a thickness of less than 100 nm. After low-energy ion thinning treatment, the sheet is observed under a high-resolution transmission electron microscope.
[0039] Selected area electron diffraction (SED) and high-resolution lattice imaging analysis were used to determine the degree of lattice distortion, dislocation density distribution, and the presence of cuprous oxide or copper oxide phases in the near-surface region. Simultaneously, energy-dispersive X-ray spectroscopy (EDS) was used to perform a surface scan of the elemental distribution to confirm whether oxygen had penetrated into the copper matrix.
[0040] The obtained microstructure information is correlated with the time-series data recorded during the testing process in a time-space backtracking manner. For example, if significant lattice distortion and high dislocation density are observed in the later stages of the test, the sudden increase in color change and rapid rise in roughness within the corresponding time period can be reasonably explained as a color change mechanism dominated by plastic deformation, rather than oxidation. This verification step ensures that the correlation revealed by the dynamic mapping function has a solid physical basis, rather than being a statistical artifact.
[0041] The entire testing process was conducted in a strictly controlled low-oxygen, constant-temperature, and constant-humidity environment. A dedicated sample stage design eliminated thermal stress deformation, a hardware-level time synchronization mechanism ensured the consistency of the time reference for multi-source data, and multimodal observation in the same region ensured spatial correspondence. The resulting time-series multidimensional dataset established for the first time a quantitative bridge between the macroscopic thermal discoloration phenomenon and the microstructural evolution of lithium-ion battery copper foil, providing irreplaceable experimental evidence for materials research and development, process optimization, and failure analysis.
[0042] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus.
[0043] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A constant temperature and humidity accelerated testing method for the thermal discoloration performance of lithium battery copper foil, characterized in that, include: The lithium battery copper foil sample to be tested is fixed on a dedicated sample stage with a built-in temperature feedback sensor; The sample stage is placed inside a constant temperature and humidity test chamber; A multispectral imaging unit, a confocal microscopy unit, and a four-probe resistance measurement unit are set in the constant temperature and humidity test chamber, and all three are aligned with the same observation area of the lithium battery copper foil sample. Start the constant temperature and humidity test program, set the target temperature and target humidity, and maintain the environmental conditions continuously acting on the lithium battery copper foil sample; After the environmental conditions stabilize, the multispectral imaging unit, confocal microscopy unit, and four-probe resistance measurement unit are activated simultaneously to continuously sample the observation area at preset time intervals. The confocal microscopy unit acquires three-dimensional surface morphology data to calculate surface roughness parameters: arithmetic mean deviation, root mean square roughness, and maximum height, and combines image processing algorithms to identify grain boundary contours and grain size distribution. The four-probe resistance measurement unit records the curve of surface resistance changing over time. The CIELab chromaticity coordinates, surface roughness parameters, grain size distribution data, and surface resistivity data are strictly aligned according to timestamps to form a unified time-series multidimensional dataset. Based on the aforementioned time-series multidimensional dataset, a dynamic mapping function is established between the color change and the surface roughness increment, the average grain size growth rate, and the surface resistivity change rate. The dedicated sample stage is made of oxygen-free copper and its surface is treated with ultra-precision polishing. A circular through hole is opened in the sample fixing area. The lithium battery copper foil sample is attached to the through hole by vacuum adsorption. The back of the sample is completely isolated from the internal environment of the cavity, and only the front is exposed to the test environment. The timestamp alignment is achieved through a hardware trigger signal. At the beginning of each sampling cycle, the main controller of the constant temperature and humidity test chamber sends a synchronous trigger pulse to the multispectral imaging unit, the confocal microscopy unit, and the four-probe resistance measurement unit. Each unit completes a single data acquisition within a delay of less than 1 millisecond after receiving the pulse.
2. The isothermal and humidity accelerated testing method for the thermal discoloration performance of lithium battery copper foil according to claim 1, characterized in that, The multispectral imaging unit uses a 16-channel filter wheel-type spectral camera, and the light source is a standard D65 sunlight simulator.
3. The isothermal and humidity accelerated testing method for the thermal discoloration performance of lithium battery copper foil according to claim 2, characterized in that, The confocal microscopy unit employs a laser scanning confocal microscope and is expanded through a stitching algorithm.
4. The isothermal and humidity accelerated testing method for the thermal discoloration performance of lithium battery copper foil according to claim 3, characterized in that, The four-probe resistance measurement unit adopts a linear four-probe configuration.
5. The isothermal and humidity accelerated testing method for the thermal discoloration performance of lithium battery copper foil according to claim 1, characterized in that, The dynamic mapping function is constructed using a multivariate nonlinear regression model, whose input variables include surface roughness. and average grain size The output variable is the amount of color change. ; The model obtains regression coefficients by fitting historical test data using the least squares method, and evaluates the model's prediction accuracy using cross-validation. The model is considered effective when the root mean square of the prediction error is less than 0.
5.
6. The isothermal and humidity accelerated testing method for the thermal discoloration performance of lithium battery copper foil according to claim 5, characterized in that, During the constant temperature and humidity test, the oxygen concentration inside the chamber is monitored in real time. The oxygen concentration is measured by an electrochemical oxygen sensor. If the oxygen concentration is greater than the threshold, the nitrogen purging program is automatically started until the concentration returns to the set range.
7. The isothermal and humidity accelerated testing method for the thermal discoloration performance of lithium battery copper foil according to claim 6, characterized in that, The thickness of the lithium-ion battery copper foil sample ranges from 4 micrometers to 8 micrometers, the initial surface roughness is controlled between 0.2 micrometers and 0.4 micrometers, and the standard deviation of the grain size distribution is less than 15% of the average value.
8. The isothermal and humidity accelerated testing method for the thermal discoloration performance of lithium battery copper foil according to claim 7, characterized in that, The method also includes the steps of preparing a cross-section of the sample and conducting transmission electron microscopy observation after the test: A thin slice with a thickness of less than 100 nanometers was cut from the center of the observation area using focused ion beam technology. The lattice distortion, dislocation density and oxide layer thickness in the near-surface region were observed using a high-resolution transmission electron microscope. The obtained microstructure information was then retrospectively correlated with the time-series data during the testing process.
Citation Information
Patent Citations
Method for measuring interface resistance of pole piece
CN113933594A
Intelligent detection system for surface quality of copper foil
CN119269507A
Method for obtaining grain orientation characteristics based on alloy etching structure optical and height characteristics
CN121838972A
